2011
DOI: 10.1103/physrevb.84.214526
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization hysteresis and time decay measurements in FeSe0.50Te0.50: Evidence for fluctuation in mean free path induced pinning

Abstract: We present results of magnetic measurements relating to vortex phase diagram in a single crystal of FeSe 0.5 Te 0.5 which displays second magnetization peak anomaly for H c. The possible role of the crystalline anisotropy on vortex pinning is explored via magnetic torque magnetometry. We present evidence in favor of pinning related to spatial variations of the charge carrier mean free path leading to small bundle vortex pinning by randomly distributed (weak) pinning centers for both H c and H ⊥ c. This is furt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 56 publications
6
30
0
Order By: Relevance
“…23,24 However, significant differences in the second-peak features have been observed within this family: in the highly anisotropic Bi-2212 and Bi-2223 the peak is sharp and temperature independent [25][26][27][28][29] while in Bi-2201 crystals it exhibits a strong temperature dependence. 30 Regarding the iron-based superconductors, the peak effect has been observed in FeAs-1111, [31][32][33] in FeAs-122, [34][35][36][37][38] and in FeTe 1−x Se x , 39 even if a clear understanding of the physical origin of the phenomenon in this family has not been achieved yet. However, since it has been shown by small angle neutron scattering, [40][41][42] Bitter decoration, 40 and magnetic force microscopy 41 that an ordered vortex lattice is not present in these compounds, the origin of the peak effect due to a phase transition of the vortex lattice seems to be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, significant differences in the second-peak features have been observed within this family: in the highly anisotropic Bi-2212 and Bi-2223 the peak is sharp and temperature independent [25][26][27][28][29] while in Bi-2201 crystals it exhibits a strong temperature dependence. 30 Regarding the iron-based superconductors, the peak effect has been observed in FeAs-1111, [31][32][33] in FeAs-122, [34][35][36][37][38] and in FeTe 1−x Se x , 39 even if a clear understanding of the physical origin of the phenomenon in this family has not been achieved yet. However, since it has been shown by small angle neutron scattering, [40][41][42] Bitter decoration, 40 and magnetic force microscopy 41 that an ordered vortex lattice is not present in these compounds, the origin of the peak effect due to a phase transition of the vortex lattice seems to be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…17 For the FeTe 0.5 Se 0.5 single crystal, it has been found that the dominant pinning mechanism is dl pinning, which is related to small bundle vortex pinning due to randomly distributed weak pinning centres. 18 Yadav et al…”
mentioning
confidence: 99%
“…The field completely penetrates into the bulk of the sample after zero field cooling. 18 The second magnetization peak (SMP) can be seen at 4 K, 7 K, and 8 K. The onset (H J c was calculated at various temperatures from these MÀH loops by using the Bean model. 21 For a rectangular shaped crystal with dimensions c < a < b, when H//c, the J c (H) is given by…”
mentioning
confidence: 99%
“…Additional and important effects are due if the material is in polycrystalline form where the grain boundary causing weak flux pinnings which limits the critical current value [33]. These issues have been extensively discussed in the Fe-based superconductors [26,27,34].…”
Section: Introductionmentioning
confidence: 99%
“…However, in all the Fe-based HTSC families will be present a second flux pinning type statistically distributed and connected to the local disorder induced by doping F, in 1111 Fe-HTSC family [26] and by composition changing between Se and Te atoms in the 11 Fe-HTSC family [27,28].…”
Section: Introductionmentioning
confidence: 99%